2010
DOI: 10.3389/fphys.2010.00143
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Frontiers in Craniofacial Reconstruction: Grand Challenges and Opportunities for the Mammalian Transforming Growth Factor-β Proteins

Abstract: Science's fascination with bone and its repair processes span for thousands of years since the ancient Greek Hippocrates, the father of Medicine, made the key discovery that bone heals without scarring. Through the centuries, several lucid investigators perceived that the extracellular matrix of bone must be a reservoir of differentiating and morphogenetic factors ultimately responsible for its pronounced healing potential (reviewed in Urist, 1968, 1994; Reddi, 2000; Ripamonti et al., 2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Calcium (Ca) plays an important role in osteoconductivity and may enhance bone tissue integration by entrapping and concentrating circulating bone growth factors (BMPs) and osteoprogenitor cells, thus imparting osteoinductive properties to calcium-based bone graft materials [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium (Ca) plays an important role in osteoconductivity and may enhance bone tissue integration by entrapping and concentrating circulating bone growth factors (BMPs) and osteoprogenitor cells, thus imparting osteoinductive properties to calcium-based bone graft materials [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ca is important for enhancing the osteoconductive properties and tissue integration of biomaterials (33). Studies have reported that higher calcium concentrations are more prone to resorption and help to compensate for the negative charges of phosphate (34).…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β3) for periodontal regeneration. The readers are directed to recent review articles for further information (reviewed in ).…”
Section: Other Growth Factors In Periodontal Regenerationmentioning
confidence: 99%